Writing a policy for use in the kidney care unit. (2nd March 2019) - Ellis, Peter; Abbott, Jane
Abstract : Policies ensure that everyone is aware of the rules that govern an activity, and, as such, they help to ensure the standardised provision of healthcare. As a kidney care leader, it may be necessary at some point to create a policy for your team, and this can be a daunting task. In this article, Peter Ellis and Jane Abbott explore what an effective policy should do, and provide some useful tips on how to write one